The mechanism of metal-based antibacterial materials and the progress of food packaging applications: A review. Issue 23 (1st December 2022) - Yang, Xiaotong; Yu, Qingjun; Gao, Wei; Tang, Xiaoning; Yi, Honghong; Tang, Xiaolong
Abstract: Food packages have been detected carrying novel coronavirus in multi-locations since the outbreak of COVID-19, causing major concern in the field of food safety. Metal-based supported materials are widely used for sterilization due to their excellent antibacterial properties as well as low biological resistance. As the principal part of antibacterial materials, the active component, commonly referred to Ag, Cu, Zn, etc., plays the main role in inhibiting and killing pathogenic microorganisms by destroying the structure of cells. As another composition of metal-based antibacterial materials, the carrier could support and disperse the active component, which on one hand, could effectively decrease the usage amount of active component, on the other hand, could be processed into various forms to broaden the application range of antibacterial materials. Different from other metal-based antibacterial reviews, in order to highlight the detailed function of various carriers, we divided the carriers into biocompatible and adsorptable types and discussed their different antibacterial effects. Moreover, a novel substitution antibacterial mechanism was proposed. The coating and shaping techniques of metal-based antibacterial materials as well as their applications in food storage at ambient and low temperatures are also comprehensively summarized. This review aims to provide a theoretical basis and reference for researchers in this field to develop new metal-based antibacterial materials.